Representações e saberes de professoras que atuam na educação de jovens e adultos em escolas municipais de Santa Maria - RS - Silva, Vera Lúcia Machado da (2008)
This study is part of the research Knowledge Formation and Professional Development carried on at the Postgraduate Program in Education at UFSM. With this work, I tried to maintain a closer contact concerning the Representations and the Knowledge of some professionals of Education who work with young and adult students in schools funded by the City Hall administration of Santa Maria. Its objective was to search for a broader comprehension about those professionals way of teaching to be able to contribute in the production of knowledge regarding the formation of teachers. A qualitative approach involving the life histories of the three teachers who collaborated in the study was conducted. By activating their memories, they were able to tell about personal and professional former experiences. Semi-structured interviews distributed in three distinguishing moments were conducted. First, I tried to become more familiar with their life histories; in a second moment, I tried to understand their representations and knowledge, and then, after the transcriptions were finished, the interviews were available for the teachers to read and give their permission to use the material. Information in relation to the questions that guide the research was collected: What kind of representations about the EJA modality do the collaborative teachers have? In which direction are those teachers mobilizing their knowledge to work with young and adult students? Which knowledge do those teachers employ to conduct their work with young and adult students? To do so, some authors are used as references, among them: Castoriadis (1986), Tardif (2002), Nóvoa (1992), Morin (2002), Freire (1999). The interviews made possible to perceive the relevance about the teachers family and initial education contexts which became important factors in the choice of their careers and in their teaching practices. In the representations about EJA student, the research revealed that both the young and the adult student are considered excluded , either because they have not been at school during the adequate period of time, or because they have been distant from the educational context. That made them become shy in the classroom and certain oral and written difficulties could be observed. The young people who come from a regular teaching process are being considered leftovers , by the majority of teachers, and are placed in EJA because of lack of discipline or inadequacy . Therefore, they show little interest and persistence. The results are originated from the exclusion inside the school itself. The adult student, even though with more difficulty, return to school aware that they need the school to keep their jobs and ascend professionally, as well as to improve their living. In face of such problems, a continued formation of young and adult educators is of the uttermost need. A large amout of teachers who lacked the correct skills during their initial formation in order to know to deal with young and adult students from lower social classes, reveal heterogeneous conceptions and employ improper practices, that is, childish practices of a compensatory nature. As to the continued formation, two aspects can be seen: on one side, an institutionalized way characterized by individual practices which reproduce disconnected knowledge from the educational context; on the other side, a constitutive way developed in a collaborative manner among students, teachers and a pedagogical teamwork in an attempt of overcoming closed and ritualistic conceptions. Thus, trough this study, the necessity of articulating continued formation in schools, which can be oriented within a more sensitive knowledge observation and can move around in a daily basis was clearly observable. A collaborative work with integrated actions for the production of knowlege and for the acknowledgement of meaning to be aware of new forms of pertinent solidarity both for teachers and students constitute one possibility to a more adequate solution with regard to the proposed issues.